Stakeholder perspectives regarding transfer of free maternity services to National Health Insurance Fund in Kenya: Implications for universal health coverage. (30th March 2018) - Abuya, Timothy; Obare, Francis; Matanda, Dennis; Dennis, Mardieh L.; Bellows, Ben
Summary: Background: Kenya is developing strategies to finance health care through prepayment to achieve universal health coverage (UHC). Plans to transfer free maternity services (FMS) from the Ministry of Health to the National Health Insurance Fund (NHIF) are a step towards UHC. We examined views of health workers and women regarding the transition of FMS to NHIF to inform the process. Methods: In‐depth interviews among 14 facility‐level managers and providers, 11 county‐level managers, and 21 focus group discussions with women who gave birth before and after the introduction of FMS. Data were analyzed thematically. Results: The transfer is a mechanism of achieving UHC, eliminating dependency on free services, and encouraging people to take responsibility of their health. However, skepticism regarding the efficiency of NHIF may limit support. Diverse and robust systems were recommended for enrollment of clients while standardization of services through accreditation and quality assurance linked to performance‐based reimbursement would improve greater predictability in the payment schedule and better coverage of referrals and complications. Conclusion: Transitioning FMS to NHIF provides an opportunity for the Ministry of Health to sharpen its role as policymaker and develop a comprehensive health care financing strategy for the country towards achieving UHC.